DI BALIK EKSISTENSI LOKALISASI DANAU TEMPE: ELIT POLITIK DAN SHADOW STATE - Kusuma Wicitra, Made Widyarini; Putra Erawan, I Ketut; Bandiyah, Bandiyah (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
The sustainability of the localization business in the Sanur area is an interesting thing in this study by explaining the power of the political elite in the existence of the localization business "Danau Tempe". The theory that the JURNAL WI author uses is Barbara Harris White's shadow state theory and Joel S. Migdal's local strongman theory. This result is to explain the power of the political elite in the existence of the localization business of "Danau Tempe." Second, the involvement of the political elite in the localization business of "Danau Tempe". Third, political elites who play a dual role are transformed into a shadow state, namely the founder and supervisor of the United Sanur Youth Association. Fourth, namely the power that underlies the relationship in the localization business of "Danau Tempe".   Keywords: Political Elite, Danau Tempe, Shadow State, Localization